2016
DOI: 10.1111/jvim.13946
|View full text |Cite
|
Sign up to set email alerts
|

New Insights in the Functional Zonation of the Canine Adrenal Cortex

Abstract: BackgroundCurrent understanding of adrenal steroidogenesis is that the production of aldosterone or cortisol depends on the expression of aldosterone synthase (CYP11B2) and 11β‐hydroxylase cytochrome P450 (CYP11B1), respectively. However, this has never been studied in dogs, and in some species, a single CYP11B catalyzes both cortisol and aldosterone formation. Analysis of the canine genome provides data of a single CYP11B gene which is called CYP11B2, and a large sequence gap exists near the so‐called CYP11B2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 59 publications
(108 reference statements)
0
17
0
1
Order By: Relevance
“…Serum progesterone and 21-deoxycortisol concentration were below the LOQ in many dogs. Sanders et al [24] reported that the high expression level of CYP17 in the zona fasciculata of canine adrenal glands and suggested that the zone-specific CYP17 expression contributed to the zone-specific cortisol production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum progesterone and 21-deoxycortisol concentration were below the LOQ in many dogs. Sanders et al [24] reported that the high expression level of CYP17 in the zona fasciculata of canine adrenal glands and suggested that the zone-specific CYP17 expression contributed to the zone-specific cortisol production.…”
Section: Discussionmentioning
confidence: 99%
“…Serum progesterone and 21-deoxycortisol concentration were below the LOQ in many dogs. Sanders et al [ 24 ] reported that the high expression level of CYP17 in the zona fasciculata of canine adrenal glands and suggested that the zone-specific CYP17 expression contributed to the zone-specific cortisol production. It may be likely that progesterone is rapidly converted to 17α-OH-progesterone and thus the serum progesterone concentration may not be enough high to be detected in the physiological condition of nonpregnant dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The SFs that were analyzed were SF-1, dosage-sensitive sex reversal-adrenal hypoplasia congenita critical region on the X chromosome gene 1 (DAX-1), and MC2R. Primers used for CYP17, HSD3B2, CYP21, MC2R, and SF-1 have been described previously [26]. New primers were designed for DAX-1 (forward 5 0 -CTTTAACCCGGACC TGC-3 0 , reverse 5 0 -GCCTGAAGAATAGCTCCAC-3 0 ).…”
Section: Reverse Transcriptase Quantitative Pcrmentioning
confidence: 99%
“…In addition to producing different steroid hormones, the zona have different cellular and topological morphologies (Vinson 2016). This zona specific synthesis (zonation) of corticosteroids persists in species with one CYP11B enzyme (Sanders et al 2016; Boon et al 1997; Schiffer, Anderko, and Hannemann 2014; Nonaka et al 1995) or those that have experienced duplications and have two CYP11B homologs (Nishimoto et al 2010; Domalik et al 1991; Ogishima et al, n.d.; Malee and Mellon 1991; Miller and Auchus 2011; Payne and Hales, n.d.; Lisurek and Bernhardt 2004; Bassett, White, and Rainey 2004). Previous work on the CYP11B homologs in primates suggests that following a duplication, the CYP11B paralogs have specialized on either 18-oxidation or 11-hydroxylation (Zöllner et al 2008; Hobler et al 2012; Strushkevich et al 2013), but none have taken a historical approach (Harms and Thornton 2013) to understand how function changed in this pathway and the mechanisms that have shaped that change.…”
Section: Introductionmentioning
confidence: 99%